THE CITY OF OSLO IN JAN ERIK VOLD’S POEMS - DUINEA, Raluca-Daniela (Studia Universitatis Babeș-Bolyai Philologia, 2021)
The City of Oslo in Jan Erik Vold’s Poems. The aim of this paper is to examine, from a cultural and social perspective, the Norwegian urban areas and everyday situations in Jan Erik Vold’s (b. 1939) poems. Our close-reading technique reveals important social aspects, different places and streets, located in the capital city of Norway, Oslo. These urban poems written by the contemporary Norwegian poet Jan Erik Vold contribute to the reconstruction of a new Norwegian cultural identity as it is reflected in a selection of poems taken from Mor Godhjertas glade versjon. Ja (Mother Goodhearted’s Happy Version. Yes, 1968), followed by the poet’s wanderings in the city of Oslo in En som het Abel Ek (One Named Abel Ek, 1988), and concluding with his bitter social criticism in Elg (Moose, 1989) and IKKE. Skillingstrykk fra nittitallet (Not: Broadsides from the Nineties, 1993). Vold’s urban poems emphasise the transition from nyenkle (new simple), friendly and descriptive poems which present closely the city of Oslo on foot, to short, political and social critical poems from the 90s. Thus, it is of great importance to traverse various urban ‘landscapes’ in different periods of time, beginning with the 1960s, followed by the 80s and the 90s. REZUMAT. Orașul Oslo în poeziile lui Jan Erik Vold. Această lucrare are ca scop o analiză, din perspectivă culturală și socială, a zonelor urbane și a situațiilor cotidiene din orașul Oslo, așa cum sunt ele prezentate în poemele lui Jan Erik Vold (n. 1939). Tehnica close-reading-ului folosită pentru a analiza acest tip de poezie urbană dezvăluie aspecte sociale importante, precum și diferite locuri și străzi din capitala Norvegiei, Oslo. Aceste poezii urbane scrise de poetul contemporan norvegian Jan Erik Vold contribuie la reconstrucția unei noi identități culturale norvegiene, așa cum este reflectată în poeziile selectate din volumul Versiunea fericită a mamei Inimă Bună. Da, 1968, urmate de plimbările poetului prin orașul Oslo, în volumul intitulat Așa-Numitul Abel Ek, 1988. Ciclul de poezii urbane se încheie cu o serie de poeme cu tenta politică, criticând aspru societatea norvegiană așa cum apar în volumele intitulate Elan, 1989 și Nu: Calomnii din anii nouăzeci, 1993. Poeziile urbane ale lui Jan Erik Vold marchează trecerea de la poeziile de tip nyenkle (neo-simpliste), deschise și descriptive, care prezintă îndeaproape orașul Oslo la pas, la poeziile critice, cu tentă politică și socială din anii ‘90. Astfel, cititorul parcurge diverse ‘peisaje’ urbane în diferite perioade de timp, începând cu anii ‘60, urmate de anii ‘80, și culminând cu anii ‘90. Cuvinte-cheie: Jan Erik Vold, poezii urbane, critica socială, zone urbane norvegiane, orașul Oslo